A genome-wide analysis of 340 318 participants identifies four novel loci associated with the age of first spectacle wear. Issue 17 (26th February 2022) - Patasova, Karina; Khawaja, Anthony P; Wojciechowski, Robert; Mahroo, Omar A; Falchi, Mario; Rahi, Jugnoo S; Hammond, Chris J; Hysi, Pirro G; ,
Abstract: Refractive errors, particularly myopia, are the most common eye conditions, often leading to serious visual impairment. The age of onset is correlated with the severity of refractive error in adulthood observed in epidemiological and genetic studies and can be used as a proxy in refractive error genetic studies. To further elucidate genetic factors that influence refractive error, we analysed self-reported age of refractive error correction data from the UK Biobank European and perform genome-wide time-to-event analyses on the age of first spectacle wear (AFSW). Genome-wide proportional hazards ratio analyses were conducted in 340 318 European subjects. We subsequently assessed the similarities and differences in the genetic architectures of refractive error correction from different causes. All-cause AFSW was genetically strongly correlated ( r g = −0.68) with spherical equivalent (the measured strength of spectacle lens required to correct the refractive error) and was used as a proxy for refractive error. Time-to-event analyses found genome-wide significant associations at 44 independent genomic loci, many of which ( GJD2, LAMA2, etc.) were previously associated with refractive error. We also identified six novel regions associated with AFSW, the most significant of which was on chromosome 17q ( P = 3.06 × 10 −09 for rs55882072), replicating in an independent dataset. We found that genes associated with AFSW were significantly enriched for expression in central nervous system tissues and were involved in neurogenesis. This work demonstrates the merits of time-to-event study design in the genetic investigation of refractive error and contributes additional knowledge on its genetic risk factors in the general population.